The role of melanocortin 1 receptor in physiological cardiac hypertrophy in mice - Suni, Aino (My University, 2024)
Melanocortin 1 receptor (MC1R) is known from its expression in the skin and regulation of skin and hair pigmentation. Recently, it has found to be expressed also in the heart, but its functional role has remained unknown. MC1R may have role in the regulation of cardiac hypertrophy, which is an adaptive response to increased cardiac workload due to exercise or cardiac disease. Exercise leads to physiological hypertrophy in which heart maintains or improves its function, whereas pathological hypertrophy occurs together with cardiovascular disease and leads to cardiac dysfunction and heart failure. Here, we examined the potential involvement of cardiomyocyte-specific MC1R signaling in regulating of physiological cardiac hypertrophy. We subjected cardiomyocyte-specific MC1R knockout mice (Mc1r cKO) and their age-matched controls to voluntary wheel running to induce physiological cardiac hypertrophy and evaluated cardiac structure and function by echocardiography, histology, quantitative PCR and Western blotting. We found that Mc1r cKO mice had lower left ventricular systolic function and increased left ventricular end-diastolic diameter compared to control mice after 5 weeks of voluntary wheel running, indicating attenuated response to exercise-induced cardiac remodeling. At the molecular level, we observed increased myosin heavy chain β (encoded by Myh7 gene) expression in the heart of Mc1r cKO mice, which could explain the disturbance in cardiac remodeling. In conclusion, cardiac MC1R signaling is involved in the regulation of physiological cardiac hypertrophy. Findings of this study may have translational significance as MC1R has several dysfunctional variants in humans, which could be associated with an impairment in exercise-induced cardiac effects.
Keywords: melanocortin 1 receptor, voluntary wheel running, physiological cardiac hypertrophy